Peranan Promosi Jabatan Dalam Meningkatkan Semangat Kerja Karyawan Pada Kantor Asuransi Jasa Indonesia (Persero) Cabang Garut Ritel - Nuryani, Eny (KarismaPro, 2023)
One of the efforts taken by the company to improve morale is to meet the promotion appropriately, because when promotions are met then the employee will contribute optimum morale. The purpose of this study is to investigate the implementation of a promotion, the condition of employee morale and job promotion role in improving employee morale at PT. Asuransi Jasa Indonesia (Persero) Branch Garut Retail.The analytical method used in this research is descriptive and verification method. Descriptive method used to determine the implementation of promotion and conditions of employee morale at PT. Asuransi Jasa Indonesia (Persero) branch of Garut Retail, the verification method used to determine the role of promotion in improving employee morale at the office of PT. Asuransi Jasa Indonesia (Persero) branch Retail Garut.The method used is survey explanation. The process of sampling carried out by random sampling technique. The sample size is 65 people. The data collection was conducted using questionnaires, interviews, and literature.These results indicate that the promotion included in the category of good, as well as morale is also high. It is seen that the coefficient of determination variable X amounted to 16.56%, and the remaining 83.44% is the influence of other factors. Spearman Rank Correlation promotion variables play a role in improving employee morale with a yield of 0,407 and have a relationship and the variables that are significant